2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487277
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive driving with model predictive path integral control

Abstract: In this paper we present a model predictive control algorithm designed for optimizing non-linear systems subject to complex cost criteria. The algorithm is based on a stochastic optimal control framework using a fundamental relationship between the information theoretic notions of free energy and relative entropy. The optimal controls in this setting take the form of a path integral, which we approximate using an efficient importance sampling scheme. We experimentally verify the algorithm by implementing it on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(237 citation statements)
references
References 18 publications
4
221
0
Order By: Relevance
“…This platform is approximately 1 meter long, weighs over 20 kilograms, and has a top speed over 20 m/s. Previous works have demonstrated that the MPPI controller (with tuned soft cost terms) is capable of navigating this type of vehicle around a simple elliptical track [25,26], which we did our best to match in our simulation experiments. Our real-world experiments use the same type of vehicle as these prior works, but in a more challenging environment (Fig.…”
Section: /5 Scale Autonomous Racing Experimentsmentioning
confidence: 78%
See 2 more Smart Citations
“…This platform is approximately 1 meter long, weighs over 20 kilograms, and has a top speed over 20 m/s. Previous works have demonstrated that the MPPI controller (with tuned soft cost terms) is capable of navigating this type of vehicle around a simple elliptical track [25,26], which we did our best to match in our simulation experiments. Our real-world experiments use the same type of vehicle as these prior works, but in a more challenging environment (Fig.…”
Section: /5 Scale Autonomous Racing Experimentsmentioning
confidence: 78%
“…For example, a number of sampling based methods have been derived using a bayesian approximate inference approach to stochastic optimal control [19,13], path integral control theory [21,8,5,25], and the cross-entropy method [4,24,10,11]. Despite all of the success in these areas, on-line sampling of trajectories with un-stable, non-linear dynamics in the presence of disturbances remains a key problem, and is usually addressed via ad-hoc cost function tuning.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…III-B. With the estimated states, we use Model Predictive Path Integral Control (MPPI) [27] in combination with a dynamics model to optimize a sequence of actions.Our proposed dynamic model is described in Sec. III-C.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these operations can be easily parallelized on a GPU [33]. Related work in model-based control for dynamic systems has utilized linear representations (e.g., Bayesian linear regression [35]), however, to the best of our knowledge, ours is the first work to develop a model-based controller the integrates a Koopman operator representation with sampling-based optimal control.…”
Section: A Model Representation and Data-driven Approximationsmentioning
confidence: 99%